Application of 5S Principles (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) for Educational Facilities and Infrastructures at SMKS Hudatul Muna 2 Ponorogo - Oktafiani, Ilmiah Sholikhah; Ahmad, Nurul Fitriyana; Ariskawanti, Eka (Proceeding International Conference on Religion, Science and Education, 2022)
The 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) principle is a Japanese work culture. This method, which places a premium on individual behaviors and awareness, has the potential to serve as a model for designing a school environment that is safe, comfortable, effective, and efficient. One of the schools that has not adhered to the 5S principles is SMKS Hudatul Muna 2 Ponorogo. This may be seen in the school’s current state, which still appears to be filthy, as well as the lack of knowledge of the importance of preserving the school’s cleanliness. This study intends to discover how to implement the 5S principles at SMKS Hudatul Muna 2 Ponorogo, as well as what should be done at SMKS Hudatul Muna 2 Ponorogo to improve the layout of educational facilities and infrastructure using 5S principles. This study combined a qualitative descriptive analytic methodology with a field research method. Data is gathered through interviews, observations, and documentation. The researcher will generate a matrix column with 5S Theory as the data analysis approach. The findings revealed that: (1) The 5S principle had not yet been implemented to the organization of educational facilities and infrastructure at Hudatul Muna 2 Vocational School in Ponorogo. (2) In preserving the cleanliness and neatness of facilities and infrastructure in schools, there is no shared sensitivity and responsibility. (3) No ongoing effort is made to organize schools in such a way that they are safe, comfortable, effective, and efficient. (4) Lack of school assistance in terms of providing facilities/supporting facilities for the implementation of the 5S culture, preventing any policy from being properly implemented. Based on the findings of the study, it can be stated that using the 5S concept can help schools manage their instructional facilities and infrastructure in a more efficient and effective manner.